PENGARUH CITA RASA, HARGA DAN CITRA MEREK TERHADAP KEPUTUSAN BERPINDAH MEREK (Survei di Desa Pakel Kecamatan Andong Kabupaten Boyolali) - Yuli Prasetyo Wibowo, Rahayu Triastity & Sunarso (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2016)
The purpose of this research was: analyzing the significance of the influence of taste, price and brand image of Mie Sedaap brand switching on a Housewife in the village of Andong Subdistrict Pakel Boyolali Regency. Analyze the dominant influence variables (taste, price or brand image) against the decision of switching brands of Mie Sedaap in Housewife in the village of Andong Subdistrict Pakel Boyolali Regency. Research methods method using survey data, the type of data used was qualitative and quantitative data, the source data used the primary data and the data of skunder. The population in this study are all mothers who never consume mie Sedaap and switching to other brands in the village of Andong Subdistrict Pakel Boyolali Regency. In this research technique sampling using the technique of purposive sampling. As for the number of samples used in the study was as many as 100 people respondents. Methods of data collection were used: questionnaires, observation and documentation. Technique of data analysis used the test of validity, reliability test, test the assumption of Linear regression analysis, classic Double, t test, F test, and the coefficient of determination. The research results obtained conclusions: there is a significant influence on the taste, price and brand image of Mie Sedaap brand switching on a Housewife in the village of Andong Subdistrict Pakel Boyolali Regency. The taste is variable, the dominant influence of switching brands of Mie Sedaap in Housewife in the village of Andong Subdistrict Pakel Boyolali Regency.Keywords: taste, price, brand image, brand switching decisions